2014
DOI: 10.1590/1677-3225v13n3a07
|View full text |Cite
|
Sign up to set email alerts
|

Bonding durability of dental sealants to deciduous and permanent teeth

Abstract: Aim: To evaluate the bonding durability of materials used as sealants on different dentitions. Methods: Deciduous (D) and permanent (P) molars were divided into four groups (n=5) and sealed with Fluroshield (F) and OptiBond FL (FL). Blocks of composite resin were built, stored in distilled water (24 h/37 °C), sectioned into 0.8 mm 2 and tested at tensile (0.5 mm/min) after 24 h and 6 months. The fractures were observed and classified into adhesive, cohesive or mixed types. The data were analyzed using repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The results showed greater adherence of the OptiBond FL at 24h, compared to Fluroshield, Clinpro TM XT and Vitremer TM , which showed a similar adhesion. This result is consistent with other studies 11,15,33,34 and can be explained by the lower viscosity of the adhesive system, as compared to other materials. OptiBond FL fulfills adequately the micro porosities of enamel produced by acid conditioning 15 , forming extensions of the material (tags) 37 that favored the adhesion.…”
Section: Micro Tensile Strength Testingsupporting
confidence: 93%
See 3 more Smart Citations
“…The results showed greater adherence of the OptiBond FL at 24h, compared to Fluroshield, Clinpro TM XT and Vitremer TM , which showed a similar adhesion. This result is consistent with other studies 11,15,33,34 and can be explained by the lower viscosity of the adhesive system, as compared to other materials. OptiBond FL fulfills adequately the micro porosities of enamel produced by acid conditioning 15 , forming extensions of the material (tags) 37 that favored the adhesion.…”
Section: Micro Tensile Strength Testingsupporting
confidence: 93%
“…While in the clinical the contamination of surface that will receive the sealant material by saliva or gingival fluid were pointed out as the main reason of failures 12 , particularities of the material used as a sealant may explain the lower adherence of some of them over time, as in the present study, which showed lower adherence of optibond FL, Fluroshield and Vitremer TM after 6 months. Moura et al 33 , in a study of longevity of adhesion of materials used as sealants, also observed a reduction in the values of the deciduous teeth sealed with optibond FL And Fluoroshield, after 6 months, suggesting that the methodology used could weaken the adhesion between the material and the dental friable enamel. In laboratory study comparing the adhesion of resinous and ionomer materials used as sealants, Papacchini et al 40 also observed higher adhesion when used resinous base materials in enamel treated with phosphoric acid, compared with glass ionomer cements after treatment with primers indicated by the manufacturers.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Sealants of pit and fissures are known as an effective method for the prevention of caries due to their properties that favor the prevention of this disease, since they act in the release of fluoride, also acting as a physical barrier between the tooth and the external environment and biocompatibility 20 . Therefore, longitudinal clinical studies should be encouraged to evaluate the efficacy of these methods 21 .…”
Section: Discussionmentioning
confidence: 99%